MASS MOBILIZATION IN THE POLITICAL SYSTEM IN VIETNAM FROM THE PAST TO THE PRESENT AND SOME ISSUES RAISED - Gam, Phan Thi Hong; Thy, Le Yen; Ha, Pham Thuy; Loan, Doan Thi Kim (American International Journal of Social Science Research, 2022)
This study aims at exploring mass mobilization in the political system in Vietnam from the past to the present and some issues raised. Studying this issue has profound political significance and social value since it reflects the relationship between classes in a certain socio-economic regime. In this study, the authors consider the following issues: i) Origin of mass mobilization; ii) Literature on mass mobilization work; iii) Mass mobilization in the political system in the past and today; iv) discussion of issues facing the mass mobilization work in the current political system in Vietnam. In this study, we have used various methods in scientific research such as analysis and synthesis, deduction and induction, abstraction and generalization, logic, history, and comparison to come to findings of the study. The current study has shown that mass mobilization work in the political system in Vietnam has been constant work and it is one of the most important factors for the victory of all Vietnamese revolutions as well as in building and protecting our nation.  JEL Classification Codes: J68, D72.